Effectiveness of Integrated Information Systems in Reporting Public Health Data: Literature Study - Sitti Hartinah; Liskha Ayuningrum; M Awaluddin; Nur Khafifah Bardi; Muhammad Asdar (Universitas Cahaya Prima, 2025)
This study aims to analyze the effectiveness of implementing Integrated Information Systems, such as the Community Health Center Management Information System (SIMPUS) and the Health Information System (SIK), in improving public health data reporting in healthcare facilities, particularly community health centers. The method used was a literature review of various studies published between 2020 and 2025. The results of the review indicate that implementing health information systems has been proven to accelerate service processes, improve data accuracy, and facilitate reporting to relevant agencies. However, implementation effectiveness is still influenced by human resources, technological infrastructure, internet network stability, and support from regional management and policies. Frequent obstacles include lack of operator training, technical system disruptions, and differences in readiness between regions. Therefore, increasing human resource capacity, strengthening infrastructure, and continuous system integration are key to achieving effective, accurate, and sustainable public health data reporting.